An LPAR5-antagonist that reduces nociception and increases pruriception - Jacqueline Langedijk; Erika Ivanna Araya; Amanda Ribeiro Barroso; Dagmar Tolenaars; Marc Nazaré; Hassane Belabed; Jens Schoene; Juliana Geremias Chichorro; Ronald Oude Elferink (Frontiers in Pain Research, 2022)
IntroductionThe G-protein coupled receptor LPAR5 plays a prominent role in LPA-mediated pain and itch signaling. In this study we focus on the LPAR5-antagonist compound 3 (cpd3) and its ability to affect pain and itch signaling, both in vitro and in vivo.MethodsNociceptive behavior in wild type mice was induced by formalin, carrageenan or prostaglandin E2 (PGE2) injection in the hind paw, and the effect of oral cpd3 administration was measured. Scratch activity was measured after oral administration of cpd3, in mice overexpressing phospholipase A2 (sPLA2tg), in wild type mice (WT) and in TRPA1-deficient mice (Trpa1 KO). In vitro effects of cpd3 were assessed by measuring intracellular calcium release in HMC-1 and HEK-TRPA1 cells.ResultsAs expected, nociceptive behavior (induced by formalin, carrageenan or PGE2) was reduced after treatment with cpd3. Unexpectedly, cpd3 induced scratch activity in mice. In vitro addition of cpd3 to HEK-TRPA1 cells induced an intracellular calcium wave that could be inhibited by the TRPA1-antagonist A-967079. In Trpa1 KO mice, however, the increase in scratch activity after cpd3 administration was not reduced.ConclusionsCpd3 has in vivo antinociceptive effects but induces scratch activity in mice, probably by activation of multiple pruriceptors, including TRPA1. These results urge screening of antinociceptive candidate drugs for activity with pruriceptors.